Frequency following response (FFR) em crianças com transtorno do desenvolvimento de linguagem - Rodrigues, Gustavo Fernando Tognini (2023)
Auditory Brainstem Response with complex sounds (cABR) allows the assessment of how behavioral sounds, such as the way speech processed in the brain. The syllable /da/ is widely used in the literature as a complex sound stimulus, and the consonant-vowel complex consists of a transient consonant segment followed by a vowel sustained periodic segment. The transient response to the consonant and the sustained response to the vowel are called the Frequency Following Response (FFR). Developmental Language Disorder (DLD) occurs when a child has severe and persistent difficulties understanding and in functioning language, which may affect daily life activities and school performance, with no other medical conditions. Children with DLD may present changes in the temporal processing of speech sounds. The FFR measures the temporal conduction capacity of the complex sound stimulus, in the auditory brainstem, without distortion. Objective: Analyse the Frequency Following Response (FFR) in children with Developmental Language Disorder. Method: Observational, cross-sectional, and prospective study. Children between four and eleven years old were invited to participate in the study and divided in two groups: the first group was composed by nine children with confirmed DLD, and nine children with typical neurological development were part of the control group. FFR data collection parameters were established, and the results were compared among the two groups. The literature with normal data was also used in order to compare the results, and ANOVA was used with this purpose. In a second moment, MATLAB engineering software was used in order to analyze the frequency domain of the FFR. Conclusion: The FFR is a viable auditory evoked potential in clinical practice with little variability of waves, in spontaneous sleep or at rest and awake. It has an important role in the evaluation of speech sound coding in the auditory brainstem, in populations with Developmental Language Disorder and Temporal Processing Disorder. The FFR´s time and frequency domain are better evaluated using the MATLAB engineering software that allows the graph